Agenda 2030 e bibliotecas públicas: implicações para a formação de leitores - Batista, Patrícia Veronesi (2021)
This dissertation integrates the studies of the line of research Education and Language, of the Postgraduate Program in Education of the Federal University of Espírito Santo, which dialogue with public policies of teaching of the Portuguese Language in Brazil, aiming to analyze reflexes of international guidelines in education Brazilian. It is part of the field of analysis of public reading policies, investigating the proposals of the Transforming Our World action plan: the 2030 Agenda for Sustainable Development, the interferences in policies directed at public libraries in Brazil and the implications for the formation of readers. The theoreticalmethodological contribution starts from conceptions originating from the Bakhtin Circle, more specifically, it resumes the conceptual categories word, sign, statement, dialogue, understanding, according to Bakhtin (2003, 2006) and polyphony, according to Bakhtin (2010). It comprises a documentary research, with a qualitative and analytical approach, dedicated to sources that show political, economic and social forces that act in international and national contexts on the areas of Education and Library Science. It contemplates contextualization, description and analysis of the sources and reveals the origins of the UN, of the sustainable development movement, as well as the neoliberal project of society, which underpin the intentions and implications of the action plan, with repercussions on the policies directed to the public libraries of the Brazil and in the training of readers. Amid the findings, pragmatic actions that focus on preparing for the job market stand out, perpetuating the contradictory and unfair social, economic and cultural order in force; the insertion of libraries to the neoliberal project, to the capitalist logic of adequacy and adaptation to the demands of the market; superficial formative processes, in search of quick results; public policies committed to the daily demands of the communities, in line with the business financing logic; and a predominantly monological discourse that tends to compromise the formation of readers, as dialogical subjects, since it disadvantages the dialogical processes that emerge from the multiplicity of voices and polyphonic discourses.